Bio-green synthesis of calcium acetate from oyster shell waste at low cost and reducing the emission of greenhouse gases - Somkiat Seesanong; Chaowared Seangarun; Banjong Boonchom; Nongnuch Laohavisuti; Somphob Thompho; Wimonmat Boonmee; Sorakit Mongkol; Pesak Rungrojchaipon (Sustainable Environment Research, 2023)
Abstract Biological wastes obtained from food, oyster shells, were recycled to calcium carbonate and then used as bio-green raw material to replace limestone/carbonate stone for calcium acetate (Ca(CH 3 COO) 2 ·H 2 O) production. The conditions (ambient temperature occurred in an exothermic reaction, drying time, yield, and solubility) of the reaction between the bio-green CaCO 3 and three different acetic (CH 3 COOH) concentrations (8, 10, and 12 M) were investigated. The product's maximum yield (93%) with a shorter drying time (18 h) was obtained from the reaction between the bio-green CaCO 3 with 12 M acetic acid revealing a lower cost. The chemical compositions without any toxic metal impurity revealed by the X-ray fluorescence technique would be useful to suggest use in the specific application. The X-ray diffraction, Fourier Transform Infrared, and Thermogravimetric analysis data of Ca(CH 3 COO) 2 ·H 2 O prepared by the bio-green CaCO 3 obtained from oyster shell wastes in this work and those in previous works used other calcium sources were consistent. The morphologies with different sizes of the obtained Ca(CH 3 COO) 2 ·H 2 O depend on the CH 3 COOH concentrations reported in this work and were different from those reported in previous works because of different calcium sources. According to the observation, it can be concluded that the low-cost and bio-green technique without the environmental effects was successfully applied to produce cheap Ca(CH 3 COO) 2 ·H 2 O and reduce greenhouse gas emissions, which can be used in the specific industry.
Keywords: Calcium Carbonate Crystallization and Inhibition; Materials Engineering and Processing; Material Selection and Properties